THE HEGEMONY OF NADHLATUL ULAMA ON POLITICAL DYNAMICS IN INDONESIA - Rian Hidayat; Qadir Gassing; Kurniati (Politea : Jurnal Politik Islam, 2024)
This study discusses the hegemony of Nahdlatul Ulama (NU) in Indonesian political dynamics by using a descriptive qualitative approach through the library research method using a sharia normative approach. Nadhalatul Ulama has strong historical roots, having a significant influence on Indonesian politics. The broad support of the community, especially Nahdliyin, allowed him to influence political policy at both the local and national levels. Through participation in the policy-making process such as the Islamic Boarding School Bill, NU brings agendas that are relevant to the interests of the community, especially in the fields of religion and education. In addition, NU plays a role in socializing democratic values through Islamic boarding schools, reflecting its contribution to strengthening the foundation of democracy at the local level. NU also acts as a counterweight in government oversight, ensuring policies are in line with people's aspirationsThe implications of this research include a better understanding of Indonesia's political dynamics and the importance of considering the role of non-state actors such as NU in the political process. It is recommended that in-depth research be conducted to broaden insights into the role of NU in Indonesian politics and society